Assessing agricultural extension agent digital readiness in Rwanda - Davis, Kristin E.; Rosenbach, Gracie; Spielman, David J.; Makhija, Simrin; Mwangi, Lucy (International Food Policy Research Institute, 2024)
Effective agricultural extension and advisory services are a key component of efforts to achieve sustainable agricultural production, resilient livelihoods, and inclusive economic growth. These are all necessary elements for accelerating Rwanda’s agricultural transformation. Both extension and information and communication technologies (ICT) are important elements in Rwanda’s Strategic Plan for Agriculture Transformation. This paper examines the capacities of public and private agricultural extension agents in Rwanda and their readiness to use ICT in their work—that is, to be digitally equipped—and provides recommendations for enhancing agricultural extension capacities through expanding and effectively using ICT. To examine capacities and readiness, we use a representative survey of 500 public and private extension agents in Rwanda, augmented by qualitative data from a literature review and key informant interviews. To assess agents’ ‘digital readiness,’ we create two indices focused on their digital experiences and attitudes toward digital modernization.